Addiction to Korean drama on purchase intention of Korean beauty products among adolescents in Malaysia / Norfaezal Abdullah Sani and Ahlam Abdul Aziz - Abdullah Sani, Norfaezal; Abdul Aziz, Ahlam (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
This study examines the relationship between addiction to Korean dramas and purchase intentions for Korean beauty products among Malaysian adolescents. A quantitative research approach was used to collect data from 120 respondents using a questionnaire. The methodology involved stratified random sampling of adolescents in Kuala Lumpur, with selections based on age, ethnicity, and exposure to Korean dramas, ensuring representative sampling and enhancing the reliability of the findings. The study aimed to assess how addiction influences purchase intentions and the broader impacts on individuals and the beauty industry. Results indicated a moderate preference for K-dramas and a corresponding purchase intent for Korean beauty products, with addiction levels significantly predicting purchase behaviours. Gender differences were observed affecting these outcomes. The findings underscore the significant impact of media exposure on adolescent consumer behaviour, highlighting potential areas for targeted interventions to foster responsible consumption. This study not only adds to the existing literature by quantifying the influence of K-drama addiction on consumer behaviour but also suggests the need for further research into media influences across different cultures and age groups.